Study of the conservation of mechanical energy in the motion of a pendulum using a smartphone. (6th December 2017) - Pierratos, Theodoros; Polatoglou, Hariton M
Abstract: A common method that scientists use to validate a theory is to utilize known principles and laws to produce results on specific settings, which can be assessed using the appropriate experimental methods and apparatuses. Smartphones have various sensors built-in and could be used for measuring and logging data in physics experiments. In this work, we propose the use of smartphones for students to study a simple pendulum's conservation of mechanical energy. It is well known that common smartphones do not have a velocity sensor, which could make the verification of the conservation of mechanical energy a simpler task. To overcome this, one can use an accelerometer to measure the centripetal acceleration on the mass and from that, deduce the maximum velocity. In this study, we show that this can be achieved with reasonable uncertainty, using a mobile device. Thus, we developed an experiment which corroborates with the conservation of mechanical energy and can be performed in the classroom.